Recent Advances in Immunotherapy in Metastatic NSCLC - Bansal, Pranshu; Osman, Diaa; Gan, Gregory N.; Simon, George R.; Boumber, Yanis (Frontiers in Oncology, 2016)
Non-small cell lung cancer (NSCLC) is one of most common malignancies and the leading cause of cancer deaths worldwide. Despite advances in targeted therapies, majority of NSCLC patients do not have targetable genomic alterations. Nevertheless, recent discovery that NSCLC is an immunogenic tumor type, and several breakthroughs in immunotherapies have led to rapid expansion of this new treatment modality in NSCLC with recent FDA approvals of PD-1 inhibitors, nivolumab and pembrolizumab. Here, we review promising immunotherapeutic approaches in metastatic NSCLC, including checkpoint inhibitors, agents with other mechanisms of action, and immunotherapy combinations with other drugs. With advent of immunotherapy, therapeutic options in metastatic NSCLC are rapidly expanding with the hope to further expand life expectancy in metastatic lung cancer.